2000
DOI: 10.1021/jp0011692
|View full text |Cite
|
Sign up to set email alerts
|

O2(aΔg) Absorption and O2(b1Σg+) Emission in Solution:  Quantifying the a−b Stokes Shift

Abstract: In a nanosecond time-resolved infrared spectroscopic study of dissolved oxygen, O 2 (a 1 ∆ g ) absorption, i.e., a 1 ∆ g f b 1 Σ g + , and O 2 (b 1 Σ g + ) emission, i.e., b 1 Σ g + f a 1 ∆ g , were monitored at ∼5200 cm -1 in a number of solvents. The maxima of the respective spectra depend significantly on the solvent, indicating that the O 2 (a 1 ∆ g ) and O 2 (b 1 Σ g + ) energy levels likewise depend significantly on the solvent. The corresponding Stokes shifts, however, are small. The latter, recorded as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(50 citation statements)
references
References 34 publications
4
46
0
Order By: Relevance
“…By default, the community invariably assumes a 1:1 complex between M and O 2 . Although it has been demonstrated computationally that such a 1:1 interaction is often sufficient to model certain phenomena (66,67), one should not exclude the likely possibility that multiple M molecules simultaneously interact with O 2 , certainly in condensed phase systems. Of course, modeling interactions with more than one M increases the complexity of the computation.…”
Section: Perturbed and Solvated Oxygenmentioning
confidence: 99%
See 2 more Smart Citations
“…By default, the community invariably assumes a 1:1 complex between M and O 2 . Although it has been demonstrated computationally that such a 1:1 interaction is often sufficient to model certain phenomena (66,67), one should not exclude the likely possibility that multiple M molecules simultaneously interact with O 2 , certainly in condensed phase systems. Of course, modeling interactions with more than one M increases the complexity of the computation.…”
Section: Perturbed and Solvated Oxygenmentioning
confidence: 99%
“…Although this so‐called dielectric continuum approach is easy to implement, and arguably accounts reasonably well for long‐range interactions between O 2 and the surrounding medium, it suffers from the obvious limitation that the all‐important short range interactions with their unique molecule‐dependent specificity are not properly implemented (66,67). This latter problem can be addressed by incorporating the concept of the M‐O 2 collision complex.…”
Section: Perturbed and Solvated Oxygenmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymer samples were mounted on the stage of a microscope (Bruker IRscopeII) attached to the FT-IR spectrometer, and the spectra were recorded from only a small spatial domain to avoid artifacts from heterogeneities (e.g., cracks, blisters) that appeared during the course of the degradation reaction. A complete description of our FT-IR spectrometer and attached microscope is provided elsewhere [25] [26]. For quantitative studies of the change in IR absorbance (e.g., Fig.…”
Section: Experimental Partmentioning
confidence: 99%
“…9 Approximately 20 years ago, we constructed a step-scan FTIR spectrometer that could record the time-resolved O 2 (a 1 Δ g ) → O 2 (b 1 Σ g + ) absorption spectrum, which occurs at ∼5200 cm −1 (i.e., ∼1925 nm) in liquid solvents. 16,17 We subsequently used this instrument to quantify solvent-dependent spectral changes in both the O 2 (a 1 Δ g ) → O 2 (b 1 Σ g + ) and 18,19 In proof-of-principle experiments, we also demonstrated that this instrument can be used to quantify k ba in a way that is useful to the study of Minaev's model for the perturbation of oxygen by liquid solvents. 20 In the present study, we modified our FTIR spectrometer to obtain a better signal-to-noise ratio and then set out to quantify O 2 (a 1 Δ g ) → O 2 (b 1 Σ g + ) absorption coefficients in a wide range of common organic solvents.…”
Section: ■ Introductionmentioning
confidence: 97%